If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+6/3=2z/4
We move all terms to the left:
2+6/3-(2z/4)=0
We add all the numbers together, and all the variables
-(+2z/4)+2+6/3=0
We add all the numbers together, and all the variables
-(+2z/4)+4=0
We get rid of parentheses
-2z/4+4=0
We multiply all the terms by the denominator
-2z+4*4=0
We add all the numbers together, and all the variables
-2z+16=0
We move all terms containing z to the left, all other terms to the right
-2z=-16
z=-16/-2
z=+8
| 10-3*x=2*x-8*x+40 | | 5p-6=6p+4-2p-10 | | -8+x/4=-5 | | (b+4)(b-3)=(b-1)(b+5)+2(b-2) | | 20v^2*80=0 | | n/4-1=0 | | Y=8/5x+7 | | -5p-10=-95 | | v+4/3=-5 | | 6+5k=6k+4 | | -3n+4=15 | | -6=w-2 | | F=-62c+32 | | n-5=5-n | | 43=8x-1+6x+15 | | 8x+6+5x=0 | | 8x+6-5x=0 | | 5(3x+8)=-5 | | (w+2)(2w-1)=(w-2)(w-5)+15 | | 2/3=a-2/9 | | 13x-15=8+2x | | -4y+4=(-2(3y+2) | | 26=(-8/5)y | | 6x+15+43=8x-1 | | (3x+24)=7x | | b/6-10=-12 | | 2n+3-n=17 | | X/6-x/3=4 | | x+2-1/3=3/4 | | 10x+13x-33=180 | | k/12-3=0 | | 3x+178=180 |